Lexical and Semantic Characteristics in the Novel "Kad su cvetale tikve" by Dragoslav Mihailović - Stevanović, Jelena M.; Milošević, Jadranka Ž.; Lazarević, Emilija N. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The creative work of Dragoslav Mihailović is included in the corpus of the SASA Dictionary, which indicates, among other things, that the prose discourse of this writer has diverse linguistic (lexical) potentials. In this context, the aim of this paper is to highlight the characteristics of the vocabulary in his novel Kad su cvetale tikve (When Pumpkins Blossomed), as well as to examine the functions that the vocabulary serves in his prose. The primary criterion applied in the analysis of the material is lexical (the source of the lexemes, their belonging to a specific thematic group, their meaning, and their role in the analyzed discourse), while the sub-criterion is semantic. The analysis indicates that the language in the given novel is primarily socially stratified and that jargonisms and jargon expressions, as well as idioms, are particularly noticeable on the lexical level. Their use is linked to the characterization of the characters and the depiction of the social reality of the time in which the work was created, but it also enhances the expressiveness and distinctiveness of the overall lexical level of this literary work. In the linguistic corpus, there is almost no dialogue without the use of sociolect, which, in a unique way, leads to the intertwining of literary-artistic and colloquial functional styles. The paper concludes that in this novel by Dragoslav Mihailović, the specific selection of vocabulary achieved not only a stylistic function but also a formal linguistic function, contributing to the overall efficiency of linguistic expression.